2015
DOI: 10.1161/strokeaha.115.010947
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Stroke or Systemic Embolism in Paroxysmal Versus Sustained Atrial Fibrillation

Abstract: A trial fibrillation (AF) is the most common cardiac arrhythmia in developed countries and increases the risks for stroke, heart failure, and death.1 Until 2 decades ago, the incidence and risk factors for stroke were less well characterized in patients with paroxysmal AF (PAF) when compared with those with persistent or permanent AF.2,3 Since then, several studies have reported that patients with PAF have a risk of thromboembolic events that was similar to that in persistent or permanent AF. [4][5][6][7] In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 25 publications
7
95
2
3
Order By: Relevance
“…The observation that persistent AF patients were more likely to have OAC has been seen in other studies. 29,30 Although the risk of stroke in paroxysmal AF is possibly lower compared with persistent or permanent AF patients, different studies reported conflict results, [31][32][33] and there is no evidence to recommend decision making for OAC in a patient by whether the subtype is persistent or paroxysmal AF. 4,5 For Nonadherence to guideline-directed OAC use may also be influenced by many variables, including the healthcare system, physician factor, and patient-level considerations.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that persistent AF patients were more likely to have OAC has been seen in other studies. 29,30 Although the risk of stroke in paroxysmal AF is possibly lower compared with persistent or permanent AF patients, different studies reported conflict results, [31][32][33] and there is no evidence to recommend decision making for OAC in a patient by whether the subtype is persistent or paroxysmal AF. 4,5 For Nonadherence to guideline-directed OAC use may also be influenced by many variables, including the healthcare system, physician factor, and patient-level considerations.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Recently, data showing a higher risk for stroke or systemic embolism in patients with persistent or permanent AF than for those with paroxysmal AF has been accumulating, mainly from post hoc analyses of large randomized controlled trials (RCTs) of oral anticoagulants (OACs) or antiplatelets for AF patients and an AF registry. [11][12][13][14] Because previous reports mainly included primary prevention cohorts; the role of AF type in the risk stratification is still unclear in secondary prevention cohorts. Furthermore, there have been little data showing the effect of AF type on initial stroke severity and clinical independence after stroke/TIA.…”
mentioning
confidence: 99%
“…The results are also reinforced by the evidence that the risk of stroke was lower in patients maintaining a paroxysmal AF pattern than those with paroxysmal AF at the baseline who progressed to a sustained AF during the 2-year follow-up (48).…”
Section: Accepted Manuscriptmentioning
confidence: 85%
“…A recent observational study conducted in Japan (48) found that paroxysmal AF was associated with a significantly higher risk of stroke than nonparoxysmal forms even after adjusting for a series of potential confounders, including oral anticoagulation. The results are also reinforced by the evidence that the risk of stroke was lower in patients maintaining a paroxysmal AF pattern than those with paroxysmal AF at the baseline who progressed to a sustained AF during the 2-year follow-up (48).…”
Section: Accepted Manuscriptmentioning
confidence: 99%